The Effect of The Number of Drugs Received On The Level of Adherence to Drug Consumption (Morisky, Green, Levine Adherence Scale Questionnaire) of Hypertensive Patients - Iin Ernawati; Selly Septi Fandinata; Silfiana Nisa Permatasari (Universitas STRADA Indonesia, 2020)
Hypertension is a chronic disease that requires long-term treatment, where it is very prone to non-adherence in taking antihypertensive drugs. This study aims to determine the effect of the number of drugs received by patients on the level of adherence to the consumption of antihypertensive drugs. This research is a cross-sectional observational study that was conducted in 4 community health centers in Surabaya City. The measurement of adherence in this study used the Indonesian version of the MGLS questionnaire. The number of subjects in this study was 143 which fit the inclusion criteria. The majority of the adherence levels of the study subjects were moderate (MGLS questionnaire). Based on statistical analysis, it is known that there is a significant effect (P = 0.035) of the number of drugs received by patients on the level of drug consumption adherence e as measured using the Indonesian version of the MGLS questionnaire.